2004
DOI: 10.1002/ajh.20221
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between the level of von Willebrand factor‐cleaving protease activity and disease in a patient with congenital thrombotic thrombocytopenic purpura

Abstract: Decreased von Willebrand factor (VWF)-cleaving protease activity (<5%) has been implicated in patients with congenital thrombotic thrombocytopenic purpura-hemolytic uremic syndrome (Upshaw-Schulman syndrome) and associated with mutations within the ADAMTS13 gene. In this report, we describe longitudinal studies in a patient with congenital TTP who ultimately developed end-stage renal failure and required plasma therapy from infancy. The patient was deficient in plasma high molecular weight (HMW)-VWF multimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…These and subsequent studies demonstrate that inhibitory autoantibodies are detectable in most patients with acquired TTP (32). Furthermore, following the first study linking hereditary TTP to mutations of the ADAMTS13 gene (4), other studies have identified more mutations in patients with the disease (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Together these two lines of evidence confirm that ADAMTS13 deficiency plays a pivotal role in causing the VWFplatelet thrombosis of TTP.…”
Section: Adamts13 Deficiency and Ttpsupporting
confidence: 64%
See 1 more Smart Citation
“…These and subsequent studies demonstrate that inhibitory autoantibodies are detectable in most patients with acquired TTP (32). Furthermore, following the first study linking hereditary TTP to mutations of the ADAMTS13 gene (4), other studies have identified more mutations in patients with the disease (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Together these two lines of evidence confirm that ADAMTS13 deficiency plays a pivotal role in causing the VWFplatelet thrombosis of TTP.…”
Section: Adamts13 Deficiency and Ttpsupporting
confidence: 64%
“…DNA nucleotide sequence analysis has detected at least 9 nonsense, 42 missense, 9 frameshifting insertion or deletion, and 6 splicing mutations (4,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). These mutations span the entire length of the protein without apparent hot spots.…”
Section: Vwf Multimer and Proteolytic Fragmentsmentioning
confidence: 99%
“…Most patients under plasmatherapy have stopped having TTP relapses. Some cases of treatment failure may have been related to insufficient amounts of plasma infused or too long an interval between infusions [19,22,32,44,77]. No role of alloimmunization anti-ADAMTS13 has ever been demonstrated.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…The mechanism is assumed to be that splenectomy decreases autoantibody production by removing a large reservoir of B lymphocytes [14], which is a reasonable explanation for patients with acquired TTP and elevated levels of ADAMTS13 inhibitor. However, Snider et al [15] reported a patient with relapsing and refractory congenital TTP who remained in complete clinical remission for 4 years after splenectomy. In our patient, remission of TTP persisted for 10 years after splenectomy, but the effect was limited.…”
Section: Discussionmentioning
confidence: 99%